2019
DOI: 10.36720/nhjk.v8i2.119
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Healthy Lifestyle Index (Hli) to the Occurrence of Hypertension in Mountains, Coastal and Urban Communities

Abstract: Background: Epidemiological transitions cause changes in disease trends from transmitted diseases to non-communicable diseases. One disease that continues to increase in prevalence and have a high-risk complication, namely hypertension. This disease has key risk factor namely lifestyle. The role of lifestyle on the incidence of hypertension is very close, especially in the community city. Surabaya has the highest prevalence of hypertension in Indonesia but has a prevalence and the role of lifestyle to the coas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…For study settings, in quantitative and mixed-method studies, 10 studies took place nationally, 24 , 41 , 47–51 , 53 , 63 , 64 19 in the urban areas, 20 , 21 , 23 , 31–33 , 36–38 , 40 , 42 , 44–46 , 52 , 54 , 55 , 58 , 76 16 in rural areas, 22 , 25–29 , 34 , 39 , 43 , 56 , 57 , 59–62 , 75 and two studies in multiple settings. 30 , 35 For quantitative studies, four of them were conducted in urban settings, 66 , 67 , 70 , 71 five were in the rural area 65 , 69 , 72–74 and one study could not be specified. 68 Overall, thirteen 22 , 26–29 , 32 , 42 , 45 , 57–60 , 64 studies have the mean age of older people as the participants (60 years old and above), whereas the rest of the studies were adults 18 years and older.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…For study settings, in quantitative and mixed-method studies, 10 studies took place nationally, 24 , 41 , 47–51 , 53 , 63 , 64 19 in the urban areas, 20 , 21 , 23 , 31–33 , 36–38 , 40 , 42 , 44–46 , 52 , 54 , 55 , 58 , 76 16 in rural areas, 22 , 25–29 , 34 , 39 , 43 , 56 , 57 , 59–62 , 75 and two studies in multiple settings. 30 , 35 For quantitative studies, four of them were conducted in urban settings, 66 , 67 , 70 , 71 five were in the rural area 65 , 69 , 72–74 and one study could not be specified. 68 Overall, thirteen 22 , 26–29 , 32 , 42 , 45 , 57–60 , 64 studies have the mean age of older people as the participants (60 years old and above), whereas the rest of the studies were adults 18 years and older.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In the quantitative and mixed-method studies, body weight management (29 studies 20 , 24 , 25 , 29 , 30 , 33 , 36 , 39–50 , 52 , 53 , 56–62 , 64 ) and physical exercise (22 studies 21 , 22 , 24 , 30–33 , 35 , 38 , 40–43 , 45 , 47 , 52 , 53 , 56 , 57 , 60 , 61 , 75 ) were the most reported, whereas in the qualitative studies, medication adherence and diet intake was the most reported self-care practice. In addition, a few studies described alternative self-care management methods such as stress-relieving methods (6 studies 35 , 40 , 60 , 66 , 68 , 75 ), sleep and rest (2 studies 68 , 74 ), and spiritual fulfilment was described in one study.…”
Section: Self-care and Lifestyle Managementmentioning
confidence: 99%
See 3 more Smart Citations